2017
DOI: 10.1111/papr.12552
|View full text |Cite
|
Sign up to set email alerts
|

Lumbopelvic Core Stabilization Exercise and Pain Modulation Among Individuals with Chronic Nonspecific Low Back Pain

Abstract: Lumbopelvic stabilization training may provide therapeutic effects by inducing pain modulation through an improvement in the pain threshold and reduction in pain intensity. LPST may be considered as part of the management programs for treatment of chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 28 publications
(39 reference statements)
5
41
0
5
Order By: Relevance
“…The improvement in TBF was three to eight times higher in terms of clinical detect-able change which ranged between 52.24% and 122.94% approximately. The observed clinical effect is comparable with other past studies that have reported improvements in TBF and PI after LPST among CLBP (21,22). Similarly, the effect of improvement in TBF after SMT was similar to a past study that re-6…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The improvement in TBF was three to eight times higher in terms of clinical detect-able change which ranged between 52.24% and 122.94% approximately. The observed clinical effect is comparable with other past studies that have reported improvements in TBF and PI after LPST among CLBP (21,22). Similarly, the effect of improvement in TBF after SMT was similar to a past study that re-6…”
Section: Discussionsupporting
confidence: 89%
“…The outcome measures for the PI and PPT were collected as per the previously established protocols (21,22). The Visual Analog Score (VAS) with a 10-cm indicator scale was used to assess the severity of the pain.…”
Section: Outcome Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol was performed three times with 30 s interval between measurements and an average value (in kPa) of the three measures was used for further analysis. 29,30 The point of measurement at the skin was marked with a semipermanent marker for the consistency of the subsequent measurements.…”
Section: Visual Analogue Scalementioning
confidence: 99%
“…Apesar das pesquisas relacionadas à reabilitação terem demonstrado a eficiência da estabilização do core nos exercícios prescritos para o auxílio no tratamento das dores nas costas e das lombalgias (PAUNGMALI et al, 2017;MAYER et al, 2016;COULOMBE et al, 2016), poucas têm sido direcionadas para examinar os benefícios para a performance de pessoas saudáveis (ANDRADES; SALDANHA, 2012).…”
Section: Introductionunclassified